Identifikasi Pemanfaatan Lahan Kawasan Tepi Danau Tempe - Misran Agustiawan; Baharuddin Koddeng; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Road to self-fringe land use inappropriate Tempe lake with the potential of a lake, the lake district looks much still used as a road to self land and serve as a shelter to retreat to the suitability inappropriate coastal areas. In addition, this region is also prone to flooding as a result of the occurrence of superficiality on Lake Tempe, as well as the provision of infrastructure in kelurahan still lacking. The purpose of this study was to identify the characteristics of land use in particular suburb of Tempe Lake Village Salomenraleng, and determine the direction of regional land use banks of Lake Tempe. Results from this study, that the retreat in villages Salomenraleng generally oriented in the riverine region. It can be seen from the distance of homes of the riverine line is only 1-2 meters. The superficiality result, some parts of the lake shore, especially in the dry season to be slowly varying functions of agricultural crops and secondary food crops. Therefore the set command ie protected areas, the initial step in the development activities carried out in the coastal lake Tempe, kelurahan Salomenrelang is to give the location of protected areas. And directed the expansion of cultivation areas land capability, among others retreat, expansion of annual crops / plantation, dry land crops and farming and fishing causeway that is a top priority.